THE RELATIONSHIP BETWEEN URBAN HEAT ISLAND ON LAND USE CHANGES AND ENVIRONMENT CRITICAL INDEX IN SEMARANG CITY - Abd Basith Mukhlas; Satya Budi Nugraha; Hariyanto Hariyanto; Heri Tjahjono (Geographica: Science and Education Journal, 2022)
The global climate problem issues have intensified lately. Many countries have agreed to reduce greenhouse gas (GHG) emissions that harm atmospheric conditions. However, fossil fuel use and a decrease in forest area continue to increase. The land use changes from vegetated to built areas could cause an environmental imbalance, primarily the urban heat island phenomenon. Semarang is one of the big cities in Indonesia with a relatively large urban area development condition. The population growth of Semarang City every year reaches an average of 1%, with population density in 2019 as much as 4,754 people per square kilometre. It makes the Semarang City area vulnerable to the urban heat island phenomenon. Moreover, the widespread use of the non-forest area is not matched by an increase in the area of green open space. The use of remote sensing technology, such as satellite imagery, is one of the solutions to monitor the urban heat island phenomenon in Semarang City and is used. Landsat 7 and 8 imagery types (Landsat Collection imagery) are used in this study to obtain the urban heat island value of Semarang City from 2003 to 2021. This study will explain how the temporal distribution pattern of the urban heat island phenomenon and the relationship between the urban heat island phenomenon and the existing land use in Semarang. This research is also equipped with an analysis of the environmental criticality index due to the impact of the urban heat island to find out more about how big the environment receives the effect.